Feasibility and Practicality of Project Based Learning Teaching Modules Based on Local Potential to Support the Implementation of the Independent High School Curriculum - Novian Indah Sari, Tasya; Rakhmawati, Anna (Jurnal Inovasi Pembelajaran Biologi, 2025)
The purpose of this study was to determine the feasibility and practicality of the Project Learning Teaching Module based on the local potential of the Gandong River on water pollution material to support the implementation of the Merdeka Curriculum in Senior High Schools. This research method is a quantitative descriptive study. The research was conducted from December 2023 to January 2024. The subjects of the study were 1) Biology learning experts, 2) Material Experts, 3) Biology Teachers, and 4) Grade X High School Students. The data collection method in this study was non-test. Non-test data in the form of expert feasibility assessment data and the practicality of the teaching module. The instruments used in this study were 1) the learning expert feasibility assessment instrument, 2) the material expert feasibility assessment instrument, 3) the teacher practicality assessment instrument, and 4) the student practicality assessment instrument. The research data were analyzed using quantitative description to obtain the percentage of feasibility and practicality of the teaching module. The results of the study showed that the PjBL teaching module based on local river potential on water pollution material for grade X received a feasible and practical assessment by learning experts and biology learning practitioners.